Polymorphism of apolipoprotein A1 gene and lipid profile of blood serum in the Evenki and Buryat populations - S. I. Kolesnikov; T. A. Bairova; O. V. Kalyuzhnaya; A. A. Trukhin; O. A. Ershova; M. A. Darenskaya (Acta Biomedica Scientifica, 2015)
The prevalence of genotypes and alleles of polymorphic markers (-75)G>A and (+83)C>T apolipoprotein A1 gene (ApOAl) in samples of ethnic groups from Eastern Siberia (the Evenkis and Buryats) were studied. In the Evenki population allele (-75)A was registered in 22,7 % cases, in the Buryat population - in 22,4 % cases. In the Evenki population allele (+83)T was found in 6,3 % cases, in the Buryat population - in 5,9 % cases. Statistically significant differences of genotypes and alleles APOA1 prevalence between the Evenkis and the Buryats was not found. The prevalence of alleles (-75)G>A and (+83)C>T of gene APOA1 obtained in the study were compared with the prevalence in different populations around the world. For each teenager in the study group we conducted a biochemical analysis of serum lipid profile. Also a comparative analysis of blood lipid profile in carriers of different genotypes was carried out. Comparative analysis of blood lipid profile in carriers of different genotypes was conducted.